2014
DOI: 10.1021/jp503788r
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Rigidity in an Intrinsically Disordered Protein, β-Casein

Abstract: The emergence of intrinsically disordered proteins (IDPs) as a recognized structural class has forced the community to confront a new paradigm of structure, dynamics, and mechanical properties for proteins. We present novel data on the similarities and differences in the dynamics and nanomechanical properties of IDPs and other biomacromolecules on the picosecond time scale. An IDP, β-casein (CAS), has been studied in a calcium bound and unbound state using neutron and light scattering techniques. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 63 publications
6
60
2
Order By: Relevance
“…Comparatively, crosslinked glycation structures including pentosidine, GOLD and MOLD can connect different protein chains together, thus limiting the flexibility of the protein chain and resulting in higher hindrance to the proteolysis . The hindrance of crosslinked glycation structure to proteolysis in this study was shown to be less significant in glycated β ‐CN, which could also be attributed to its intrinsic flexible and open structure …”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Comparatively, crosslinked glycation structures including pentosidine, GOLD and MOLD can connect different protein chains together, thus limiting the flexibility of the protein chain and resulting in higher hindrance to the proteolysis . The hindrance of crosslinked glycation structure to proteolysis in this study was shown to be less significant in glycated β ‐CN, which could also be attributed to its intrinsic flexible and open structure …”
Section: Resultsmentioning
confidence: 66%
“…By contrast, the DH value of β ‐CN glycated with 10 mmol L −1 glucose did not show a significant decrease in either gastric or intestinal digestion. This finding may be related to the intrinsic disordered structure of β ‐CN . The flexible structure and high thermal stability of β ‐CN may weaken hindrance induced by glycation structures to the action of digestive proteases.…”
Section: Resultsmentioning
confidence: 98%
“…The side chain dynamics depend on the length and polarity of the amino acid residue, as well as on the chemical environment of the side chain, which in turn is determined by the folding of the entire protein chain. Accordingly, an unfolded polypeptide chain is more flexible than a tightly folded globular protein [50,51]. …”
Section: Resultsmentioning
confidence: 99%
“…As before, we reduce the charge on nESI generated protein ions and examine the CCSDs of precursor and product ions. We compare the structural change when the charge is reduced for a rigid (BPTI) [48, 49] and for an intrinsically disordered protein (beta casein) [50–52]. …”
Section: Introductionmentioning
confidence: 99%